2009
DOI: 10.1105/tpc.109.071514
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Meiotic Crossovers Coexist in Maize

Abstract: We apply modeling approaches to investigate the distribution of late recombination nodules in maize (Zea mays). Such nodules indicate crossover positions along the synaptonemal complex. High-quality nodule data were analyzed using two different interference models: the "statistical" gamma model and the "mechanical" beam film model. For each chromosome, we exclude at a 98% significance level the hypothesis that a single pathway underlies the formation of all crossovers, pointing to the coexistence of two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 58 publications
4
60
0
Order By: Relevance
“…Crossovers visualized by MLH1 foci represent type I crossovers, i.e., those that show interference (Mercier et al 2015). In maize, mathematical modeling indicated that about 80% of the crossovers as assessed by RNs are type I crossovers with the remaining RNs (not labeled by MLH1) being type II crossovers, i.e., those that do not show interference (Falque et al 2009;Mercier et al 2015). Based on these results and an average of about 20 RNs per nucleus (Anderson et al 2003), one would expect an average of about (0.8 3 20) 16 MLH1 foci per nucleus in maize.…”
Section: Discussionmentioning
confidence: 99%
“…Crossovers visualized by MLH1 foci represent type I crossovers, i.e., those that show interference (Mercier et al 2015). In maize, mathematical modeling indicated that about 80% of the crossovers as assessed by RNs are type I crossovers with the remaining RNs (not labeled by MLH1) being type II crossovers, i.e., those that do not show interference (Falque et al 2009;Mercier et al 2015). Based on these results and an average of about 20 RNs per nucleus (Anderson et al 2003), one would expect an average of about (0.8 3 20) 16 MLH1 foci per nucleus in maize.…”
Section: Discussionmentioning
confidence: 99%
“…The ν values vary between 0 (no interference) to 20 (absolute interference, or only 1 crossover per chromosome) [Falque et al, 2009;Gauthier et al, 2011]. The distances were fitted to gamma distributions by a maximum-likelihood method.…”
Section: Methodsmentioning
confidence: 99%
“…Current evidence in yeast and other organisms indicates that MLH1 foci tag the CO events showing chiasmatic interference, while a second type of COs (non-interfering) follows a molecular pathway lacking MLH1 [reviewed in Mezard et al, 2015]. As shown in a number of plants and animals, the proportion of non-interfering COs varies from species to species, accounting for 5-30% of all CO events [de Boer et al, 2006;Falque et al, 2009]. The presence of 2 classes of COs in birds has not yet been tested, but both RNs and MLH1 foci show CO interference in birds [Pigozzi and Solari, 1997;Pigozzi, 2001].…”
Section: Crossover Markers Along Avian Scsmentioning
confidence: 99%